Open letter to the President Dilma Rousseff - Passos, Mauro Romero Leal (Brazilian Journal of Sexually Transmitted Diseases, 2010)
I read in The Globe 05.02.2011, page 13, a story on the subject. Data already well known, were once again cited: in Brazil, 4.800 women a year die of cervical cancer and 18.430 more women are affected of the same evil. [...]